PENGARUH PROFESIONALISME KERJA DAN KOMITMEN TERHADAP KINERJA KARYAWAN DIVISI PENDIDIKAN PONDOK PESANTREN HAJI YA’QUB LIRBOYO KEDIRI - Arifin, Muhammad; Meilina, Restin; Sardanto, Rino (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This assessment aims to determine the variables between work professionalism and commitment to employee performance at the Haj Ya'qub Lirboyo Islamic boarding school, Kediri. This study uses a quantitative approach, with primary data distributed directly to the respondents. The sample in this study was the Board of Directors of the Hajj Ya'qub Lirboyo Islamic Boarding School, Kediri, consisting of 50 people. By using validity, reliability, classical assumptions, multiple linear regression analysis, hypothesis testing, by using the t test and F test, with the help of the SPSS 26 program. The results of this study partially state that work professionalism with a sig value of 0.000 has an effect on employee performance and commitment with sig 0.086 has a negative effect on employee performance. Simultaneously work professionalism and commitment affect employee performance with a sig value of 0.000